MULTIPLEX EVALUATION OF ConA-INDUCED PRODUCTION OF TWELVE CYTOKINES IN THE CULTURES OF MONONUCLEAR CELLS FROM PERIPHERAL BLOOD OF HEALTHY SUBJECTS - Konenkov, V. I.; Avdoshina, V. V.; Rakova, I. G.; Smolninkova, M. V.; Gelfgat, E. L. (Medit͡s︡inskai͡a︡ immunologii͡a, 2014)
The goal of this work was a multiplex single-step evaluation of the levels of stimulated cytokine production in the supernates of cultivated mononuclear cells from healthy Caucasian individuals. We compared the levels of cytokines for various groups. In Th1 cells, the production of INF-γ is typically greater than production of IL-2. Analysis of Th2-derived cytokines demonstrated predominance of IL-10 production over other cytokines. Furthermore, we observed in healthy donors a significantly stronger production of IL-13 as compared to IL-4. These cytokines function as co-stimulators of proliferation for pre-activated B-cells.When performing pairwise comparisons of the growth factor concentrations, we have shown higher levels of G-CSF production than that of GM-CSF, thus reflecting predominance of differentiation stimuli for granulocytopoiesis over monocytopoiesis in bone marrow of healthy humans.Among pro-inflammatory cytokines tested, the significantly higher TNF-α production is prevalent. Low levels of ConA stimulated IL-7 production from the bone marrow stromal cells, which activates complete differentiation of T- and B-lymphocyte progenitors, might be due to low mitogen activity for the non-lymphoid cells.